Epidermal lamellar bodies, essential organelles for the skin barrier - Corinne Leprince; Michel Simon (Frontiers in Cell and Developmental Biology, 2025)
Skin lamellar bodies are members of the Lysosome-Related-Organelle (LRO) family, characterized by specific features related to the skin’s primary function, i.e., protecting the body from external assaults while minimizing dehydration. In the uppermost living cell layers of the epidermis, the vesicles and tubulovesicular network that make up the « lamellar body system » as identified by electron microscopists, play a crucial role in maintaining the skin barrier. As a secretory compartment, lamellar bodies carry a variety of compounds that, when released in the extracellular space or exposed at the membrane, contribute to the unique hydrophobic structure of the upper epidermis (lipids and lipid metabolism enzymes), regulate desquamation (proteases and inhibitors) and provide anti-microbial defense. The molecular machinery involved in the biogenesis and trafficking of skin lamellar bodies is only beginning to be deciphered, including the Rab11A GTPase, the Myosin5B molecular motor, and the CHEVI complex. This later one is constituted of the Vps33B and VIPAR tethering molecules, whose mutations lead to the ARC and ARKID syndromes. Further studies are needed to identify the key molecules regulating the various stages of LB biogenesis, maturation and exocytosis. It is likely that some of these molecules will be shared with other members of the LRO family. These studies will further enhance our understanding of the relationships between lamellar body trafficking and skin barrier dysfunction.